Perfil proteico de mycobacterium tuberculosis após a exposição a etambutol e eupomatenóide-5 - Ghiraldi-Lopes, Luciana Dias (2017)
Tuberculosis (TB) is a chronic infectious disease caused by the bacillus Mycobacterium tuberculosis (M. tb). In recent years, just a low number of new effective compounds against M. tb had emerged, which motivates researches with drugs already used in the treatment of TB and also the search for new therapeutic options. Ethambutol (EMB) is a drug used in the first scheme of TB treatment and works inhibiting arabinosyl transferases which prevents the biosynthesis of arabinogalactan. The substance eupomatenoid-5 (EUP-5), is a neoligan isolated extracted from genus Piper with antimicrobial activity including anti-M. tb activity. The aim of this study was to evaluate the proteomic profile of M. tb after EMB and EUP-5 induction using two-dimensional electrophoresis coupled to mass spectrometry and to construct protein interaction networks using the STRING-10 database. This evaluation was divided into two papers. In the first manuscript 'Proteomic approach brings new knowledge about the targets of Ethambutol in Mycobacterium tuberculosis' the reference strain M. tb H37Rv was induced to sub inhibitory concentration of EMB for 24 h and 48 h. The major protein changes occurred in proteins of intermediate metabolism and respiration indicating that these proteins can also be explored as drug targets. The second article was named 'Protein profile of Mycobacterium tuberculosis after induction by eupomatenoid-5 reveals potential drug targets'. A proteomic and morphological analysis of M. tb H37Rv was performed after 12 h, 24 h and 48 h of EUP-5 induction to the sub inhibitory concentration. EUP-5 was able to promote the rounding and wrinkled appearance of bacilli and the main protein changes occurred after 24 h in proteins related to intermediate metabolism, lipid metabolism, virulence and detoxification, information proteins and cellular processes with some mycobacteria-specific proteins. The construction of networks of protein interactions by the STRING-10 database is an efficient tool which allows a better visualization of the impact caused by EMB and EUP-5 in M. tb and demonstrated the interaction of multiple proteins that were responsible for disorders in the metabolism and consequent death of the bacilli .